Revisiting the Biological Behavior of Salmonella enterica in Hydric Resources: A Meta-Analysis Study Addressing the Critical Role of Environmental Water on Food Safety and Public Health - Rocha, Alan Douglas de Lima; Ferrari, Rafaela Gomes; Pereira, Walter Esfrain; Lima, Laiorayne Araújo de; Givisiez, Patrícia Emília Naves; Moreno-Switt, Andrea Isabel; Toro, Magaly; Delgado-Suárez, Enrique Jesús; Meng, Jianghong; Oliveira, Celso José Bruno de (Frontiers in Microbiology, 2022)
The increasing number of studies reporting the presence of Salmonella in environmental water sources suggests that it is beyond incidental findings originated from sparse fecal contamination events. However, there is no consensus on the occurrence of Salmonella as its relative serovar representation across non-recycled water sources. We conducted a meta-analysis of proportions by fitting a random-effects model using the restricted maximum-likelihood estimator to obtain the weighted average proportion and between-study variance associated with the occurrence of Salmonella in water sources. Moreover, meta-regression and non-parametric supervised machine learning method were performed to predict the effect of moderators on the frequency of Salmonella in non-recycled water sources. Three sequential steps (identification of information sources, screening and eligibility) were performed to obtain a preliminary selection from identified abstracts and article titles. Questions related to the frequency of Salmonella in aquatic environments, as well as putative differences in the relative frequencies of the reported Salmonella serovars and the role of potential variable moderators (sample source, country and sample volume) were formulated according to the population, intervention, comparison, and outcome method (PICO). The results were reported according to the Preferred Reporting Items for Systematic Review and Meta-Analyzes statement (PRISMA). A total of 26 eligible papers reporting 148 different Salmonella serovars were retrieved. According to our model, the Salmonella frequency in non-recycled water sources was 0.19 [CI: 0.14; 0.25]. The source of water was identified as the most import variable affecting the frequency of Salmonella, estimated as 0.31 and 0.17% for surface and groundwater, respectively. There was a higher frequency of Salmonella in countries with lower human development index (HDI). Small volume samples of surface water resulted in lower detectable Salmonella frequencies both in high and low HDI regions. Relative frequencies of the 148 serovars were significantly affected only by HDI and volume. Considering that serovars representation can also be affected by water sample volume, efforts towards the standardization of water samplings for monitoring purposes should be considered. Further approaches such as metagenomics could provide more comprehensive insights about the microbial ecology of fresh water and its importance for the quality and safety of agricultural products.